2018
DOI: 10.1097/ta.0000000000001975
|View full text |Cite
|
Sign up to set email alerts
|

Can acute care surgeons perform while fatigued? An EAST multicenter study

Abstract: Prognostic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In another study, approximately 600 cases have roughly similar results, in regard to mortality and morbidity outcomes of the surgeries that been performed by fatigued and non-fatigued surgeons. However, the nub of the argument, is that rested surgeons who were more likely to perform on older or female patients, they concluded that the outcomes were similar for fatigued and rested surgeons, [ 9 ] which we think brought the same debate back to surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, approximately 600 cases have roughly similar results, in regard to mortality and morbidity outcomes of the surgeries that been performed by fatigued and non-fatigued surgeons. However, the nub of the argument, is that rested surgeons who were more likely to perform on older or female patients, they concluded that the outcomes were similar for fatigued and rested surgeons, [ 9 ] which we think brought the same debate back to surface.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Other studies concluded that the outcomes were similar for fatigued and rested surgeons. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…This study compared outcomes for complex emergency surgery cases between fatigued surgeons (no sleep in the prior 18 h) and non-fatigued surgeons (slept at least 3 out of the last 6 h). There was no difference in mortality or post-operative complications between the two groups [ 5 ]. Although patient outcomes may be unaffected, more work hours per week, fewer awake hours at home, and number of call shifts per week have been associated with poor physician work-life balance and burnout among trauma surgeons [ 2 , 3 ].…”
Section: Physical Wellnessmentioning
confidence: 99%
“…dures being performed, all operations were classified on an ordinal scale of complexity from 1 to 4. 20 Case complexity was assigned independently by 2 surgeons (K.M.S. and B.B.)…”
Section: Key Pointsmentioning
confidence: 99%
“…We hypothesized that outcomes may be improved with increased surgeon experience and undertook this secondary analysis of a previously reported cohort study. 20…”
mentioning
confidence: 99%